School innovation climate as a driver of teachers’ innovative work behavior: the mediating role of self-efficacy - Mokhlis, Safiek; Abdullah, Abdul Hakim (Institute of Advanced Engineering and Science, 2025)
Teachers’ innovative work behavior (IWB) is widely recognized as a driving force behind educational improvement in the complex and demanding conditions of the 21st century. Among a wide range of factors that could affect IWB, innovation climate (IC) has emerged as a crucial determinant. However, research exploring the mechanism that mediate the link between IC and IWB is still limited. Drawing upon social cognitive theory (SCT), the present study proposes that teachers’ self-efficacy (SE) acts as a mediator in the relationship between IC and IWB. The study involved 376 teachers at 12 public schools in Kuala Terengganu, Malaysia, who were determined based on a stratified random sampling technique. Analysis of data was implemented through the use of structural equation modeling (SEM) with AMOS software to test causal relationships. Results confirmed that schools’ IC was positively correlated with IWB and that this relationship was partially mediated by teachers’ SE. These results align with SCT, which emphasizes the interaction between individual behavior, environment (IC), and personal factors (SE). To cultivate a culture of innovation and improve educational outcomes, school leaders should actively foster an IC that enhances teachers’ SE, thereby promoting their IWB.